High-temperature-resistant soft magnetic composite material for integrated inductor and preparation method thereof
Patent Information
- Application Number
- CN202611174365.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-27
AI Technical Summary
其一,采用耐高温特种环氧树脂,虽可提升耐温等级,但材料成本大幅上升,且树脂粘度高,包覆均匀性差,成型工艺窗口窄;
1、本发明提供了一种一体成型电感用耐高温软磁复合材料及其制备方法,铁硅铬基复合材料在170℃高温老化1050小时后,感值变化率从纯环氧体系的11.03%降至4.39%,降幅超过60%,远优于AEC-Q200标准要求,可满足更严苛的车规级高温工况,并且有机硅树脂添加量低,复合材料的密度、磁导率、压溃强度、饱和偏置特性等核心性能与纯环氧体系基本持平,不会因耐温提升牺牲磁性能与机械性能,器件电气设计无需调整。
Smart Images

Figure CN122991789A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of soft magnetic functional composite materials and electronic component manufacturing technology, specifically to a high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method. Background Technology
[0002] With the rapid evolution of consumer electronics towards miniaturization, high frequency, and high power density, and the explosive growth of the new energy vehicle industry, the performance and reliability requirements of passive components in electronic systems continue to increase. Molded inductors, with their advantages of fully shielded structure, low leakage flux, low noise, small size, and large saturation current, have become core passive components in high-power DC-DC circuits.
[0003] Especially in the field of automotive electronics, inductor products need to meet the AEC-Q200 automotive-grade reliability standard, which requires continuous operation for 1,000 hours in a high-temperature environment of 155°C, with inductance value fluctuations controlled within 10%; some high-end automotive scenarios even require long-term high temperatures above 170°C.
[0004] The magnetic cores of existing integrally molded inductors are mainly made by combining soft magnetic metal powder with thermosetting binders such as epoxy resin, and then cold-pressing them. The long-term service temperature of conventional epoxy resin binders is usually around 125℃. During long-term high-temperature aging, the resin molecular chains are prone to oxidative degradation and cross-linking breakage, leading to a decrease in adhesion, gradual release of internal stress, and changes in the spacing and arrangement of magnetic powder particles. Ultimately, this causes a significant drift in inductance value, and in severe cases, even problems such as magnet cracking and appearance failure, which cannot meet the high-temperature reliability requirements of automotive-grade inductors.
[0005] To improve high-temperature resistance, existing solutions in the industry mainly fall into three categories: Firstly, while using high-temperature resistant special epoxy resin can improve the temperature resistance level, it significantly increases the material cost, and the resin has high viscosity, poor coating uniformity, and a narrow molding process window. Secondly, although inorganic binders such as glass and ceramics have excellent temperature resistance, they have high molding pressure and poor mechanical toughness, making them prone to brittleness and unable to be adapted to existing cold pressing molding processes. Third, increasing the thickness of the insulating coating layer will lead to a decrease in the magnetic powder filling rate, a significant deterioration in magnetic permeability and saturation current, and a sacrifice in device performance.
[0006] Therefore, developing a one-piece molded soft magnetic composite material for inductors that can significantly improve high-temperature aging stability and is compatible with existing cold pressing processes without significantly increasing costs or degrading magnetic and mechanical properties is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method. By introducing a small amount of organosilicon resin into an epoxy resin binder system for blending modification, the high bond energy characteristics of the organosilicon Si-O backbone are utilized to improve the overall temperature resistance of the binder, suppress resin degradation and stress release during high-temperature aging, and significantly improve the inductance stability under long-term high temperatures while maintaining the original magnetic properties, mechanical strength, and molding process compatibility, meeting the high reliability requirements of automotive-grade products. At the same time, the cost increase is controllable and suitable for mass production.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A high-temperature resistant soft magnetic composite material for integrally molded inductors comprises, by weight: 100 parts soft magnetic metal powder, 4.2-4.8 parts organic hybrid insulating binder, and 8 parts organic solvent; The organic hybrid insulating adhesive is obtained by blending and modifying high-temperature resistant epoxy resin and organosilicon resin, wherein the mass of organosilicon resin is 0.2% to 0.8% of the soft magnetic metal powder.
[0009] Furthermore, the soft magnetic metal powder is one or a mixture of several of the following: iron-silicon-chromium alloy powder, carbonyl iron powder, amorphous iron powder, and nanocrystalline iron powder.
[0010] Furthermore, the soft magnetic metal powder is Fe with a D50 of 10 μm. 92 Si3.5Cr4.5 iron-silicon-chromium alloy powder, or carbonyl iron powder with D50=5μm, or a mixture of the two in a certain proportion.
[0011] Furthermore, the high-temperature resistant epoxy resin is one of bisphenol A modified high-temperature resistant epoxy resin and phenolic modified epoxy resin; the organosilicon resin is methylphenyl organosilicon resin with a solid content ≥50%.
[0012] Furthermore, in the organic hybrid insulating adhesive, the mass ratio of high-temperature resistant epoxy resin to organosilicon resin is 4:(0.2~0.8).
[0013] Furthermore, the composite material undergoes a 6T / cm test. 2 After pressure cold pressing, the material density is 5.6~6.5 g / cm³. 3 The initial permeability at 1MHz is 22~29, and the radial crushing strength is ≥40MPa.
[0014] Furthermore, the integrally molded inductor prepared using iron-silicon-chromium alloy powder exhibits a change rate of ≤5% in inductance value relative to its initial value after aging at 170℃ for 1000 hours.
[0015] Furthermore, an integrally molded inductor is prepared by cold pressing an enameled coil, using the high-temperature resistant soft magnetic composite material described in any one of claims 1 to 7 as the magnetic core body.
[0016] Furthermore, a method for preparing a high-temperature resistant soft magnetic composite material for integrally molded inductors includes the following steps: Step S1: Adhesive premixing High-temperature resistant epoxy resin and organosilicon resin are added to an organic solvent in a certain proportion and stirred evenly at room temperature to obtain a uniform and transparent hybrid adhesive solution. Step S2: Mixing and Granulation Soft magnetic metal powder is added to a hybrid binder solution and stirred at high speed until the powder is uniformly coated to obtain a wet mixture. The mixture is then granulated by shaking to obtain granular wet material. Step S3: Drying treatment The granulated wet material is spread evenly on a tray and placed in an electric oven at 60°C for 60 minutes to dry completely remove residual organic solvents, thus obtaining the finished soft magnetic composite powder.
[0017] Furthermore, the method also includes a cold pressing step: placing the finished soft magnetic composite powder and the built-in coil together into a molding die, pressing at 5~6T / cm 2 The unit pressure is used for cold pressing and holding to form an integral inductor blank; after forming, no additional high-temperature curing process is required, and subsequent termination and packaging can be carried out directly.
[0018] This invention provides a high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method. It has the following beneficial effects: 1. This invention provides a high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method. After aging at 170°C for 1050 hours, the inductance change rate of the iron-silicon-chromium-based composite material decreases from 11.03% in the pure epoxy system to 4.39%, a reduction of more than 60%, which is far superior to the AEC-Q200 standard requirements. It can meet more stringent automotive-grade high-temperature operating conditions. Moreover, the amount of silicone resin added is low, and the core properties of the composite material, such as density, permeability, crush strength, and saturation bias characteristics, are basically the same as those of the pure epoxy system. The magnetic and mechanical properties are not sacrificed due to the increase in temperature resistance, and the electrical design of the device does not need to be adjusted.
[0019] 2. This invention provides a high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method. Only a small amount of organosilicon resin needs to be added to the raw materials to achieve an upgrade in temperature resistance. The main materials and process routes do not need to be changed, and the increase in material cost is less than 5%, which is far lower than that of special epoxy or inorganic binder solutions, and has extremely high cost performance.
[0020] 3. This invention provides a high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method. The preparation process is fully compatible with the traditional cold-pressing integral molding process, requiring no new equipment, no production line modification, and no additional high-temperature curing process. It can be directly connected to existing large-scale production lines, resulting in low mass production introduction costs. The modification scheme is compatible with various mainstream soft magnetic powders such as iron-silicon-chromium, carbonyl iron powder, and amorphous powder. The powder system can be flexibly selected according to product performance requirements, and the application scenarios cover a full range of products from small consumer inductors to high-power automotive inductors. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the microstructure of the high-temperature resistant soft magnetic composite material of the present invention; Figure 2 This is a schematic diagram of the overall process flow for the preparation method of the high-temperature resistant soft magnetic composite material of the present invention; Figure 3 The curves show the rate of change of sensitivity at 170°C for different embodiments and comparative examples of the present invention. Detailed Implementation
[0022] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not intended to limit it. Furthermore, it should be noted that, for ease of description, the accompanying drawings show only the parts relevant to the present invention, and not all of the structures.
[0023] In the description of this invention, unless otherwise explicitly specified and limited, the terms "connected," "linked," and "fixed" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0024] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can include direct contact between the first and second features, or contact between the first and second features through another feature between them. Furthermore, "above," "over," and "on top" of the second feature includes the first feature directly above or diagonally above the second feature, or simply indicates that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature includes the first feature directly below or diagonally below the second feature, or simply indicates that the first feature is at a lower horizontal level than the second feature.
[0025] In the description of this embodiment, the terms "upper," "lower," "right," etc., refer to the orientation or positional relationship shown in the accompanying drawings. They are used only for ease of description and simplification of operation, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the present invention. In addition, the terms "first" and "second" are used only for distinction in description and have no special meaning.
[0026] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0027] like Figures 1-3 As shown, this embodiment of the invention provides a high-temperature resistant soft magnetic composite material for integrally molded inductors, which consists of three parts: soft magnetic metal powder, organic hybrid insulating binder, and organic solvent. The function and design principle of each component are as follows: Soft magnetic metal powder serves as the magnetic functional matrix of the composite material, providing soft magnetic properties such as high magnetic permeability and high saturation magnetic induction. One or more of the following can be used in combination: iron-silicon-chromium alloy powder, carbonyl iron powder, amorphous iron powder, and nanocrystalline iron powder. Iron-silicon-chromium alloy powder: Excellent corrosion resistance, low high-frequency loss, and good DC bias characteristics, suitable for medium and high power inductors; Carbonyl iron powder: high purity, fine particles, high magnetic permeability, and good formability, making it suitable for small-volume, high-inductance inductors.
[0028] The powder particle size is controlled at the micron level to ensure good molding density and uniformity of magnetic properties.
[0029] Organic hybrid insulating binder is the structural phase of composite material. On the one hand, it forms a uniform insulating coating layer on the surface of magnetic powder particles, reducing eddy current loss; on the other hand, it provides mechanical bonding strength after cold pressing, maintaining the stability of the magnet structure.
[0030] This invention employs a hybrid system modified by blending high-temperature resistant epoxy resin and organosilicon resin: High-temperature resistant epoxy resin: As the main binder, it has excellent bonding performance, molding fluidity and mechanical strength, and strong adhesion to the magnetic powder surface, ensuring the strength and dimensional accuracy of the green body after cold pressing. Organosilicon resin: As a temperature-resistant modifier, its molecular backbone is composed of Si-O bonds, with bond energies much higher than C-C bonds. It has excellent thermal oxidation stability and is not easily degraded or broken at high temperatures. After blending, it can form a high-temperature resistant phase in the binder system, improve the overall temperature resistance, reduce resin degradation and internal stress release during high-temperature aging, stabilize the bonding state between magnetic powder particles, and thus suppress inductance drift.
[0031] The amount of silicone resin added should be controlled at 0.2% to 0.8% of the magnetic powder mass. A small amount of addition can achieve a significant improvement in temperature resistance, while avoiding the problems of reduced adhesion and deterioration of moldability caused by excessive silicone.
[0032] Acetone is selected as the organic solvent to adjust the viscosity of the binder, so that the binder can be evenly coated on the surface of each magnetic powder, ensuring granulation flowability and molding uniformity; it can be completely evaporated after drying, leaving no residue.
[0033] The preparation method of this integrally molded inductor high-temperature resistant soft magnetic composite material includes the following steps: Step S1: Adhesive premixing First, the epoxy resin and silicone resin are thoroughly mixed in acetone solvent to form a uniform hybrid binder solution, ensuring that the two resins are dispersed at the molecular level and avoiding uneven coating in the subsequent process. Step S2: Mixing and Granulation The soft magnetic powder and binder solution are mixed at high speed to make the binder uniformly coat the surface of the magnetic powder particles; then the particles are granulated by shaking to form a uniform granular wet material, which improves the molding fluidity and filling uniformity. Step S3: Drying treatment Low-temperature drying removes residual acetone solvent, yielding a dry composite powder that can be directly used for cold pressing. Step S4: Cold pressing The composite powder and the built-in coil are placed into a mold together, and then cold-pressed and held under a set pressure. The resin itself binds to form a complete one-piece inductor preform without the need for an additional high-temperature curing process.
[0034] High-temperature aging resistance modification principle: The core mechanism of this invention to achieve high-temperature aging resistance lies in the synergistic effect of organic-organic hybrid binders: Under long-term aging at 170℃, the epoxy groups and molecular side chains of the pure epoxy resin system are prone to oxidative breakage, the cross-linking network is destroyed, the adhesion decreases, the internal pressure of the magnet is gradually released, the spacing between magnetic powder particles increases, and the inductance value continues to rise.
[0035] After the introduction of organosilicon resin, the Si-O bond energy reaches as high as 452 kJ / mol, which is much higher than the 347 kJ / mol of the C-C bond, making it more stable at high temperatures. The organosilicon phase is uniformly dispersed in the epoxy matrix, forming an interpenetrating network structure. On the one hand, it blocks oxygen diffusion and slows down the oxidative degradation of epoxy. On the other hand, it undertakes part of the bonding effect, maintaining the bonding strength and structural stability at high temperatures, reducing the stress release rate, and thus significantly reducing the sensitivity change rate after long-term high-temperature aging.
[0036] The present invention will be further described in detail below with reference to specific embodiments, comparative examples and performance tests. These embodiments are only used to explain the technical solutions of the present invention and do not limit the scope of protection of the present invention.
[0037] Example 1: Low-addition organosilicon modified iron-silicon-chromium composite material In this embodiment, the amount of silicone resin added is 0.2% of the magnetic powder mass, and the specific preparation steps are as follows: S1: Adhesive premix Weigh 4 parts of epoxy resin and 0.2 parts of silicone resin according to the mass ratio, add them to 8 parts of acetone solvent, stir at 300 rpm for 20 minutes at room temperature until the solution is homogeneous and transparent, and obtain the hybrid adhesive solution.
[0038] S2: Mixing and Granulation Weigh 100 parts of iron-silicon-chromium alloy powder and add it to the mixer. Slowly pour in the hybrid binder solution and stir at high speed for 15 minutes until the powder is evenly coated. Transfer the wet mixture to the swing granulator and granulate to obtain wet particles with a particle size of 0.2~1mm.
[0039] S3: Drying process The wet granules are evenly spread on a tray with a layer thickness of ≤2cm. The tray is placed in an oven at 60℃ for 60 minutes. After cooling, the powder is sieved to obtain the finished soft magnetic composite powder.
[0040] S4: Cold pressing Take an appropriate amount of composite powder and put it into the mold, at 6T / cm 2 The magnetic ring sample and the 0420-100 specification integrally molded inductor sample were prepared by cold pressing and holding at unit pressure for 30s.
[0041] Example 2: Medium-to-low addition of organosilicon-modified iron-silicon-chromium composite material In this embodiment, the amount of silicone resin added is 0.4% of the magnetic powder mass, and the specific preparation steps are as follows: S1: Adhesive premix Weigh 4 parts of epoxy resin and 0.4 parts of silicone resin according to the mass ratio, add them to 8 parts of acetone solvent, stir at 300 rpm for 20 minutes at room temperature until the solution is homogeneous and transparent, and obtain the hybrid adhesive solution.
[0042] S2: Mixing and Granulation Weigh 100 parts of iron-silicon-chromium alloy powder and add it to the mixer. Slowly pour in the hybrid binder solution and stir at high speed for 15 minutes until the powder is evenly coated. Transfer the wet mixture to the swing granulator and granulate to obtain wet particles with a particle size of 0.2~1mm.
[0043] S3: Drying process The wet granules are evenly spread on a tray with a layer thickness of ≤2cm. The tray is placed in an oven at 60℃ for 60 minutes. After cooling, the powder is sieved to obtain the finished soft magnetic composite powder.
[0044] S4: Cold pressing Take an appropriate amount of composite powder and put it into the mold, at 6T / cm 2 The magnetic ring sample and the 0420-100 specification integrally molded inductor sample were prepared by cold pressing and holding at unit pressure for 30s.
[0045] Example 3: Optimal addition amount of organosilicon-modified iron-silicon-chromium composite material In this embodiment, the amount of silicone resin added is 0.6% of the magnetic powder mass, and the specific preparation steps are as follows: S1: Adhesive premix Weigh 4 parts of epoxy resin and 0.6 parts of silicone resin according to the mass ratio, add them to 8 parts of acetone solvent, stir at 300 rpm for 20 minutes at room temperature until the solution is uniform and transparent, and obtain the hybrid adhesive solution.
[0046] S2: Mixing and Granulation Weigh 100 parts of iron-silicon-chromium alloy powder and add it to the mixer. Slowly pour in the hybrid binder solution and stir at high speed for 15 minutes until the powder is evenly coated. Transfer the wet mixture to the swing granulator and granulate to obtain wet particles with a particle size of 0.2~1mm.
[0047] S3: Drying process The wet granules are evenly spread on a tray with a layer thickness of ≤2cm. The tray is placed in an oven at 60℃ for 60 minutes. After cooling, the powder is sieved to obtain the finished soft magnetic composite powder.
[0048] S4: Cold pressing Take an appropriate amount of composite powder and put it into the mold, at 6T / cm 2 The magnetic ring sample and the 0420-100 specification integrally molded inductor sample were prepared by cold pressing and holding at unit pressure for 30s.
[0049] Example 4: High-content organosilicon-modified iron-silicon-chromium composite material In this embodiment, the amount of silicone resin added is 0.8% of the magnetic powder mass, and the specific preparation steps are as follows: S1: Adhesive premix Weigh 4 parts of epoxy resin and 0.8 parts of silicone resin according to the mass ratio, add them to 8 parts of acetone solvent, stir at 300 rpm for 20 minutes at room temperature until the solution is homogeneous and transparent, and obtain the hybrid adhesive solution.
[0050] S2: Mixing and Granulation Weigh 100 parts of iron-silicon-chromium alloy powder and add it to the mixer. Slowly pour in the hybrid binder solution and stir at high speed for 15 minutes until the powder is evenly coated. Transfer the wet mixture to the swing granulator and granulate to obtain wet particles with a particle size of 0.2~1mm.
[0051] S3: Drying process The wet granules are evenly spread on a tray with a layer thickness of ≤2cm. The tray is placed in an oven at 60℃ for 60 minutes. After cooling, the powder is sieved to obtain the finished soft magnetic composite powder.
[0052] S4: Cold pressing Take an appropriate amount of composite powder and put it into the mold, at 6T / cm 2 The magnetic ring sample and the 0420-100 specification integrally molded inductor sample were prepared by cold pressing and holding at unit pressure for 30s.
[0053] Example 5: Organosilicon-modified carbonyl iron composite material In this embodiment, the amount of silicone resin added is 0.6% of the magnetic powder mass, and the specific preparation steps are as follows: S1: Adhesive premix Weigh 4 parts of epoxy resin and 0.6 parts of silicone resin according to the mass ratio, add them to 8 parts of acetone solvent, stir at 300 rpm for 20 minutes at room temperature until the solution is uniform and transparent, and obtain the hybrid adhesive solution.
[0054] S2: Mixing and Granulation Weigh 100 parts of carbonyl iron powder and add it to the mixer. Slowly pour in the hybrid binder solution and stir at high speed for 15 minutes until the powder is uniformly coated. Transfer the wet mixture to the swing granulator and granulate to obtain wet particles with a particle size of 0.2~1mm.
[0055] S3: Drying process The wet granules are evenly spread on a tray with a layer thickness of ≤2cm. The tray is placed in an oven at 60℃ for 60 minutes. After cooling, the powder is sieved to obtain the finished soft magnetic composite powder.
[0056] S4: Cold pressing Take an appropriate amount of composite powder and put it into the mold, at 6T / cm 2 The magnetic ring sample and the 0420-100 specification integrally molded inductor sample were prepared by cold pressing and holding at unit pressure for 30s.
[0057] Comparative Example 1: Pure epoxy system iron-silicon-chromium composite material This comparative example does not add silicone resin, and the rest of the formulation and preparation process are exactly the same as in Example 1. The formulation is: 100 parts of iron-silicon-chromium powder, 4 parts of epoxy resin, and 8 parts of acetone.
[0058] Comparative Example 2: Carbonyl Iron Composite Material Based on Pure Epoxy System This comparative example does not add silicone resin, and the rest of the formulation and preparation process are exactly the same as in Example 5. The formulation is: 100 parts carbonyl iron powder, 4 parts epoxy resin, and 8 parts acetone.
[0059] Performance testing: Standardized performance tests were performed on the samples from Examples 1-5 and Comparative Examples 1-2. The average value of 5 samples was taken for each test. The test method is as follows: Bulk density: The bulk density of the magnetic ring sample was tested using the Archimedes displacement method; Initial permeability: The initial permeability was calculated by measuring the inductance value at 1MHz and 0V bias using an impedance analyzer. Saturation retention rate: The ratio of permeability to zero bias is measured by superimposing a 100Oe DC bias field. Radial crushing strength: The radial crushing force of the magnetic ring was tested using a universal testing machine, and the crushing strength was calculated. High-temperature aging inductance value change rate: The inductor sample was placed in a 170℃ high-temperature test chamber and taken out and cooled to room temperature after 350h, 600h, 900h and 1050h respectively. The inductance value at 1MHz was tested and the change rate relative to the initial value was calculated: Change rate = (aging inductance value - initial inductance value) / initial inductance value × 100%.
[0060] The test results of the basic characteristics of the magnetic ring are shown in the table below: The test results of the change rate of aging sensitivity at 170℃ are shown in the table below: Results analysis: 1. Effect of Organosilicon Addition on Temperature Resistance: For the iron-silicon-chromium system, as the amount of organosilicon resin added increases from 0 to 0.6%, the change rate of sensitivity after 1050 hours of aging continuously decreases from 11.03% to 4.39%, indicating a significant improvement in temperature resistance. When the addition amount increases to 0.8%, the change rate of sensitivity slightly rebounds. This is because: an appropriate amount of organosilicon can effectively improve the temperature resistance of the binder and inhibit stress release; however, excessive organosilicon will reduce the interfacial bonding force between epoxy and magnetic powder, thus accelerating interfacial failure. Therefore, the optimal addition amount is 0.6% of the magnetic powder mass.
[0061] 2. Basic Magnetic and Mechanical Properties Analysis: After adding organosilicon, the material density and magnetic permeability decreased slightly, with the decrease within 5%, which is within an acceptable range; the saturation retention rate increased slightly, while the crushing strength remained basically the same. This proves that a small amount of organosilicon modification does not degrade the core performance of the material, and the overall performance is balanced, making it a direct replacement for the original material.
[0062] 3. Differences between different powder systems: The sensitivity of carbonyl iron powder itself tends to decrease after aging, and the decrease is slightly greater after adding organosilicon. This is because carbonyl iron powder particles are fine and have high internal stress, and stress release during aging is mainly through shrinkage; organosilicon improves the bonding strength and inhibits the increase in sensitivity caused by stress relaxation, but the regulation of shrinkage-type changes is different. In practical applications, the amount of organosilicon added needs to be adjusted according to the aging trend of the powder itself, and the improvement effect is optimal for systems with increasing sensitivity.
[0063] 4. Reliability verification: After aging at 170℃ for 1050 hours, the optimal formula in Example 3 showed a sensitivity change rate of only 4.39%, which is far lower than the industry's general requirement of 10%, fully meeting the automotive-grade AEC-Q200 standard, and can even be adapted to more stringent high-temperature conditions of 170℃.
[0064] The above embodiments and comparative examples fully verify the effectiveness of the technical solution of the present invention: by using a small amount of silicone resin to modify epoxy resin binder, the change rate of the 170°C high-temperature aging inductance value of the iron-silicon-chromium-based integral molded inductor can be reduced by more than 60% without significantly affecting the magnetic properties, mechanical properties and processability, thus greatly improving high-temperature reliability.
[0065] This invention offers a low-cost, high-performance material solution for automotive-grade high-reliability integrally molded inductors, with minimal cost increase, strong process compatibility, and good mass production adaptability. It possesses extremely high industrial application value and economic benefits.
[0066] The following points should be noted in this article: 1. The accompanying drawings of the embodiments disclosed herein only relate to the structures involved in the embodiments disclosed herein; other structures can be referred to in a general design.
[0067] 2. Where there is no conflict, the embodiments of this disclosure and the features in the embodiments can be combined with each other to obtain new embodiments.
[0068] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A high-temperature resistant soft magnetic composite material for integrally molded inductors, characterized in that, By weight, it includes: 100 parts soft magnetic metal powder, 4.2-4.8 parts organic hybrid insulating binder, and 8 parts organic solvent; The organic hybrid insulating adhesive is obtained by blending and modifying high-temperature resistant epoxy resin and organosilicon resin, wherein the mass of organosilicon resin is 0.2% to 0.8% of the soft magnetic metal powder.
2. The high-temperature resistant soft magnetic composite material for integrally molded inductors according to claim 1, characterized in that, The soft magnetic metal powder is one or a mixture of several of the following: iron-silicon-chromium alloy powder, carbonyl iron powder, amorphous iron powder, and nanocrystalline iron powder.
3. The high-temperature resistant soft magnetic composite material for integrally molded inductors according to claim 2, characterized in that, The soft magnetic metal powder is Fe with a D50 of 10 μm. 92 Si3.5Cr4.5 iron-silicon-chromium alloy powder, or carbonyl iron powder with D50=5μm, or a mixture of the two in a certain proportion.
4. The high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method according to claim 1, characterized in that, The high-temperature resistant epoxy resin is one of bisphenol A modified high-temperature resistant epoxy resin and phenolic modified epoxy resin; the organosilicon resin is methylphenyl organosilicon resin with a solid content ≥50%.
5. The high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method according to claim 1, characterized in that, In the organic hybrid insulating adhesive, the mass ratio of high-temperature resistant epoxy resin to organosilicon resin is 4:(0.2~0.8).
6. The high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method according to claim 1, characterized in that, The composite material is subjected to 6T / cm 2 After pressure cold pressing, the material density is 5.6~6.5 g / cm³. 3 The initial permeability at 1MHz is 22~29, and the radial crushing strength is ≥40MPa.
7. The high-temperature resistant soft magnetic composite material for integrally molded inductors and its preparation method according to claim 1, characterized in that, The integrally molded inductor made of iron-silicon-chromium alloy powder has a change rate of ≤5% in inductance value relative to the initial value after aging at 170℃ for 1000 hours.
8. A molded inductor, characterized in that, The magnetic core is prepared by cold pressing an integral molding process using the high-temperature resistant soft magnetic composite material described in any one of claims 1 to 7 as the main body of the magnetic core and an embedded enameled coil.
9. A method for preparing a high-temperature resistant soft magnetic composite material for integrally molded inductors, characterized in that, Includes the following steps: Step S1: Adhesive premixing High-temperature resistant epoxy resin and organosilicon resin are added to an organic solvent in a certain proportion and stirred evenly at room temperature to obtain a uniform and transparent hybrid adhesive solution. Step S2: Mixing and Granulation Soft magnetic metal powder is added to a hybrid binder solution and stirred at high speed until the powder is uniformly coated to obtain a wet mixture. The mixture is then granulated by shaking to obtain granular wet material. Step S3: Drying treatment The granulated wet material is spread evenly on a tray and placed in an electric oven at 60°C for 60 minutes to dry completely remove residual organic solvents, thus obtaining the finished soft magnetic composite powder.
10. The method for preparing the high-temperature resistant soft magnetic composite material for integrally molded inductors according to claim 9, characterized in that, The method further includes a cold pressing step: the finished soft magnetic composite powder and the built-in coil are placed together in a molding die at a pressure of 5~6T / cm. 2 The unit pressure is used for cold pressing and holding to form an integral inductor blank; after forming, no additional high-temperature curing process is required, and subsequent termination and packaging can be carried out directly.